Document Management Application Design At Pt X - Dhian Satria Yudha Kartika; Renanda Auzan Firdaus (International Journal of Computer, Network Security and Information System, 2023)
Documents are one of the most important assets for the sustainability of a company. However, to manage documents properly, it is necessary to have a system that can assist in managing documents related to the company. PT X feels the need to have an application that can help manage company documents effectively and efficiently. Therefore, PT X decided to design a document management application. This application is designed to assist in managing documents related to the company. In addition, this application will also assist in the process of borrowing company documents.This document management application will consist of several main features, including document management features, user data management features, document loan management features, and reporting features. The document management feature will help you manage company documents in an organized and structured manner, making it easier to find the documents you need.After carrying out the design and build of this document management application, it is expected that PT X can be more effective and efficient in managing company documents. Thus, PT X will be able to improve the performance and productivity of its employees, as well as make it easier to manage the documents it has.